P176 Real-world use of the IBD Disk tool for evaluation of patient-reported disability in the outpatient clinic. (25th January 2019) - Savelkoul, E; Sharma, N; Disney, B; Shah, A; de Silva, S; Iacucci, M; Ghosh, S; Cooney, R
Abstract: Background: The IBD disability index (IBD-DI) is a validated healthcare professional (HCP) administered tool that can assess the functional status of patients in trials. The IBD-Disk was adapted from the IBD-DI as a tool that patients can use to capture their functional status for HCPs to review. We report patient acceptability and the use of the IBD-disk in the real-world setting. Methods: The IBD-Disk was constructed by an expert steering committee of 30 international gastroenterologists/nurses who ranked the IBD-DI items. An IBD-DI working group of 14 gastroenterologists used a modified Delphi process to agree on 10 IBD-Disk items. Inclusion criteria comprised patients aged 18 and over, of all ethnicities, with a confirmed diagnosis of CD/UC. Exclusion criteria were lack of fluency in English, not agreeable to take part or participation was deemed inappropriate. Patients were asked to rate their level of agreement for each item on the IBD Disk on a visual analogue scale of 0–10 (0 = absolutely NO, 10 = definitely YES). We included a difficulty rating of 1–10 to assess ease of completion of the questionnaire (1 = very easy; 10 = very difficult) as well as qualitative feedback. Results: A total of 200 patients took part. The mean age of the cohort was 41 years. 113 (58%) were female. 167 were White, 6 Indian, 9 Asian, 14 Other, 4 did not specify. Fifty per cent of patients had CD, 41% had UC and 9% were unclassified. Of the domains of the IBD disk (Table 1, Figure 1), energy levels and joint pain scored highest (most impairing) with mean values of 5.71 and 4.90, , respectively, whereas interpersonal interactions and sexual functions were least affected, mean scores 2.54 and 2.62. The mean difficulty rating was 2.2. Significant correlation was found between abdominal pain and energy levels/sleep ( r = 0.60 and r = 0.55; p < 0.01) and between joint pain and energy levels/sleep (both r =0.56; p < 0.01). We accounted for steroid use and noted no significant effect on sleep, energy or emotions. Clinicians highlighted that the IBD disk opened up conversations beyond GI issues and gave a good overview of well-being. Patients' feedback highlighted that they were glad they were able to express their functional status Mean (SD) scores for each IBD-disk item. Visual representation of IBD disk scores demonstrating disease burden. Conclusions: Energy levels and joint pain were the most disabling for this unselected IBD cohort. Our first experience with the IBD-Disk proved very positive.